ANALYSIS OF MOTIVATION AND NON-COGNITIVE PERSONALITIES IN ENGLISH ACHIEVEMENT AND GLOBAL COMPETENCES: THE CASE OF AGRICULTURE STUDENTS - Dian Islami Prasetyaningrum; Hafida Ruminar; Asihing Kustanti; Putra Irwandi (University of Kuningan, 2023)
The ability to speak English is essential to compete in global competition. As a provision in this competition, honing global competence must get attention. Good English skills and the knowledge related to the capacity to identify cultural differences and willingness to interact with other people are also critical. The success of mastering these abilities cannot be separated from the role of individual personality and learning motivation as factors that influence the success of educational outcomes. This research aimed to discover the influence of non-cognitive personality that moderates students' motivation to learn English, which also affects the achievement of English learning outcomes and global competence. The non-cognitive personalities are taken from Goldberg's Big Five Personality Traits (1992), namely Openness to new experiences (Openness), conscientiousness, enthusiasm for socializing (extraversion), compliance (agreeableness), and mental stability (Neuroticism). The research used an online survey of 304 First Year Faculty of Agriculture students who took English courses. The data analysis used descriptive qualitative study. The results obtained showed that extraversion personality dominantly influences the motivational variable. Meanwhile, the global competence and skills variables are dominated by Openness. Lastly, the global knowledge variable is dominated by Neuroticism.